A broadly cross-reactive monoclonal antibody against hepatitis E virus capsid antigen - Kubickova, Barbara; Schenk, Jörg A.; Ramm, Franziska; Markuškienė, Kornelija; Reetz, Jochen; Dremsek, Paul; Tamosiunas, Paulius Lukas; Cepulyte, Laima; Trinh, Hoai Anh; Scholz, Johannes; Memczak, Henry; Hovestädt, Marc; et al. (2021)
To generate a hepatitis E virus (HEV) genotype 3 (HEV-3)–specific monoclonal antibody (mAb), the Escherichia coli–expressed carboxy-terminal part of its capsid protein was used to immunise BALB/c mice. The immunisation resulted in the induction of HEV-specific antibodies of high titre. The mAb G117-AA4 of IgG1 isotype was obtained showing a strong reactivity with the homologous E. coli, but also yeast-expressed capsid protein of HEV-3. The mAb strongly cross-reacted with ratHEV capsid protein derivatives produced in both expression systems and weaker with an E. coli–expressed batHEV capsid protein fragment. In addition, the mAb reacted with capsid protein derivatives of genotypes HEV-2 and HEV-4 and common vole hepatitis E virus (cvHEV), produced by the cell-free synthesis in Chinese hamster ovary (CHO) and Spodoptera frugiperda (Sf21) cell lysates. Western blot and line blot reactivity of the mAb with capsid protein derivatives of HEV-1 to HEV-4, cvHEV, ratHEV and batHEV suggested a linear epitope. Use of truncated derivatives of ratHEV capsid protein in ELISA, Western blot, and a Pepscan analysis allowed to map the epitope within a partially surface-exposed region with the amino acid sequence LYTSV. The mAb was also shown to bind to human patient–derived HEV-3 from infected cell culture and to hare HEV-3 and camel HEV-7 capsid proteins from transfected cells by immunofluorescence assay. The novel mAb may serve as a useful tool for further investigations on the pathogenesis of HEV infections and might be used for diagnostic purposes. Key points • The antibody showed cross-reactivity with capsid proteins of different hepeviruses. • The linear epitope of the antibody was mapped in a partially surface-exposed region. • The antibody detected native HEV-3 antigen in infected mammalian cells.